Penyuluhan Pencegahan Covid-19 Dengan Menjaga Protokol Kesehatan Di RT 01 Kelurahan Tondo: Penyuluhan Pencegahan Covid-19 Dengan Menjaga Protokol Kesehatan Di RT 01 Kelurahan Tondo - Afrina Januarista; Siti Magfirah; Irna; Darul Fahri; Suci Nurain; Sandhy Aditya Arsadana; Apriani Soleman; Tri Nuri Damayanti; Nur Afni Febrianty; Anita Pratiwi Ranti; Deysy Arisandi Masulili; Melsandy Aggraeni (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Coronavirus Disease 2019 (COVID-19) is a new type of disease that has never been previously identified in humans. The virus that causes Covid-19 is called Sars-CoV-2. This covid-19 counseling and prevention is carried out so that we know about Covid-19 and how to prevent and handle it, especially for people who live around RT 01 who are very vulnerable to Covid-19 transmission due to the lack of people maintaining health protocols. This activity aims to provide education and assistance to the community around RT 01 to implement health protocols to avoid the transmission of Covid-19. The approach method used in this community service activity is in the form of outreach to the community about preventing Covid-19 through education and a participatory approach, meaning that participants are required to be active in participating during the activity. The activity process is in the form of counseling through education with material delivered in the form of powerpoints and educational videos and is interspersed with the distribution of masks and hand washing fluids during the activity. The activity was carried out on Tuesday, March 1, 2022 at RT 01 RW 05, Tondo Village. The result of this activity is increasing public knowledge regarding the importance of maintaining health protocols and ways to prevent transmission of the Covid-19 virus. It is hoped that by conducting this outreach, the public will be more aware and concerned about preventing Covid-19 by wearing masks. In addition, all people when leaving the house wear masks